(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Iron deficiency anemia (IDA) remains a global health challenge, particularly among women of childbearing age, due to menstrual blood loss and increased iron demands during pregnancy. While traditional diagnostic methods such as serum ferritin and hemoglobin assays are valuable, they may lack sensitivity in detecting advanced stages of IDA. This review explores recent advancements in diagnostic techniques for identifying and characterizing advanced IDA in women of childbearing age. Innovations such as novel biomarkers, advanced imaging modalities, and artificial intelligence-based algorithms offer promising avenues for earlier and more accurate diagnosis, enabling timely intervention and improved patient outcomes. Furthermore, this review discusses the clinical implications, challenges, and future directions in integrating these innovative approaches into routine clinical practice.